REPRODUCTIVE BIOLOGY OF NATURAL BETTA FISH (Betta picta) IN THE GENDING MERTOYUDAN RIVER, MAGELANG REGENCY - Fadila Rizmauliana; Tholibah Mujtahidah; Andri Nofreeana (JURNAL AKUAKULTURA, 2025)
Natural betta fish is one of the Betta fish that comes from nature and still has high genetic diversity because it has not been crossed with cultivated Betta fish. Many environmental changes affect the reproduction of natural betta fish in their natural habitat, so it is necessary to carry out studies related to the reproductive biology of natural betta fish (Betta picta). This research aims to determine various reproductive biology and the influence of water quality on the gonad maturity level of natural betta fish (B. picta). The research was conducted from October to November 2023 in the Gending River, Mertoyudan District, Magelang Regency, and the Integrated Laboratory of Tidar University. Fish samples were caught using a seser and placed in plastic containers for observation in the laboratory. The gonad maturity level, or GMI, was observed morphologically and analyzed descriptively. The results of this research were that the TKG consisted of TKG I-TKG V, the IKG value was 4.7%, the IG value was 48.2, the HSI value was 0.7%, the sex ratio was 1:1, the relationship between length and weight was allometric negative, and plankton abundance was 166.6ind/l. There was an increase in the second week of observation up to the sixth week.